UNIT 8.16 Using ClinVar as a Resource to Support Variant Interpretation. (1st April 2016) - Harrison, Steven M.; Riggs, Erin R.; Maglott, Donna R.; Lee, Jennifer M.; Azzariti, Danielle R.; Niehaus, Annie; Ramos, Erin M.; Martin, Christa L.; Landrum, Melissa J.; Rehm, Heidi L.
Abstract : ClinVar is a freely accessible, public archive of reports of the relationships among genomic variants and phenotypes. To facilitate evaluation of the clinical significance of each variant, ClinVar aggregates submissions of the same variant, displays supporting data from each submission, and determines if the submitted clinical interpretations are conflicting or concordant. The unit describes how to (1) identify sequence and structural variants of interest in ClinVar by multiple searching approaches, including Variation Viewer and (2) understand the display of submissions to ClinVar and the evidence supporting each interpretation. By following this protocol, ClinVar users will be able to learn how to incorporate the wealth of resources and knowledge in ClinVar into variant curation and interpretation. © 2016 by John Wiley & Sons, Inc.